Validação da versão em Libras do instrumento para avaliação da qualidade de vida de pessoas com deficiências físicas e intelectuais (WHOQOL-DIS/Libras) - Freitas, Adriana Ribeiro de (2016)
Introduction: The access to information and to the possibility of communication in language sign is dealt in the World Report on Disability by World Health Organization (WHO) as a disabling barrier faced by the deaf person, which harms his social, emotional, and cognitive development and reduces his quality of life. Currently, the evaluation of those people‟s quality of life is limited to the instruments based on the oral languages. However, in order to evaluate the quality of life of deaf people who communicate through sign language, it is necessary to have instruments which consider their cultural and linguistic differences. In Brazil, the right to communicate in their natural language, the Brazilian Sign Language (Libras), has been guaranteed to the deaf person since 2002, according to the Law n. 10.436, without imposition of the use the major language of the country. Objective: The objective of the study is to validate the Libras version of the instrument to evaluate the quality of life of people with physical and intellectual disabilities (WHOQOL-DIS). Methods: The participation in the research took place in a virtual space accessed by the electronic address www.medicina.ufg.br/qualidadedevida, which hosts the software that contains the research instruments – in the period from April 25th 2015 to June 25th 2015. Deaf associations from various cities in Brazil, universities which offer the Libras Language course and Pastoral movements of deaf have been contacted for data collection, and social media groups, such as Facebook and Whatsapp, have been created. It is a cross-sectional, descriptive, and quantitative study which makes use of traditional psychometric methods to conduct the analysis of the WHOQOL-DIS/Libras validity and trustworthiness. Its utilization has been tested in a field trial with 311 deaf people, from 18 to 65 years old, who communicate through Libras and belong to the Brazilian deaf community. Among them, 52 were retested in a 15-day interval. Results: The WHOQOL-DIS/Libras trustworthiness has been demonstrated by the Cronbach‟s alpha (internal consistency) satisfactory statistical values and by the Temporal Stability (test-retest). It has presented discriminant competence in the variables „years of study‟, „gender, and „income‟, but not in the variable „age‟. In the variable „health perception‟, it has demonstrated capacity to measure the construct. The confirmatory factor analysis showed reasonable item adjustments. Conclusion: Therefore, this research found evidence of the validity and trustworthiness of the instrument WHOQOL-DIS/Libras to evaluate the quality of life of deaf people.